A Literature Review on Non-planar PDC Cutter - Chen, Lian; Fu, Zhiqiang (International Journal of Mechanical and Electrical Engineering, 2025)
Since the introduction of PDC bits in 1973, significant advancements have been achieved in drilling efficiency. However, to address the diverse requirements of various formation rocks—such as differences in hardness, strong abrasiveness, and heterogeneity—and to further enhance drilling performance, several companies worldwide have continuously improved upon conventional cylindrical PDC cutters. These efforts have led to the development of a series of innovative geometric designs for novel-shaped PDC cutters. This paper focuses on an investigation of non-planar cutters. It begins by introducing the application background of non-planar cutters and analyzing the current research status and development trends related to non-planar cutters and the rock-breaking mechanisms of PDC, both domestically and internationally. Furthermore, various types of non-planar cutters are enumerated, and their characteristics are described in detail. Regarding the research methodology for non-planar PDC cutters, this paper elaborates on the procedural steps—from the analysis of the rock-breaking mechanism of PDC cutters, to the evaluation of their rock-cutting performance, and finally to experimental analysis. This systematic approach provides valuable guidance for the rational design of non-planar PDC cutters.